31 Patent bibliometric analysis of bio/pharma cold-chain logistics in China. (19th December 2016) - Liu, Zhenfeng; Feng, Jian
Abstract : Objectives: Our objectives are to study the development and historical evolution of the bio/pharma cold-chain logistics industry in China. Bio/pharma cold-chain logistics has attracted a large number of scholars whose research has resulted in patents. Cold-chain modes like cold-chain transportation, cold-chain circulation, low temperature and multi-modal transportation have played an important role in bio/pharma cold-chain logistics. The implementation of cold-chain logistics also guarantees that the bio/pharma will always be kept at a low temperature state during the circulation process. The highlighted issues of drug safety make this more important. Statistically, the rates of cold-chain circulation and cold-chain transportation in China are 20% and 30%, compared to more than 90% in developed countries. Therefore, it is necessary for scholars to carry out scientific research on cold-chain logistics. Methods: A scientific literature database including a patent information services platform was used. Data visualization methods such as a patent management map, quantitative methods and bibliometrics were used to study patents. Results: The results revealed that the bio/pharma literature and cold-chain logistics technologies have increased substantially. Institutes and universities are the main forces behind basic research, and bio/pharma enterprises have begun to focus on intellectual property protection and technological innovation. Conclusions: Institutes and enterprises should be encouraged to carry out cooperative research on bio/pharma cold-chain logistics, to promote cold-chain resource integration and transfer to the Midwest, and to strengthen bio/pharma enterprises to speed up investment in the secondary market in China. Acknowledgments: This research was financially supported by the Foundation of Philosophy and Social Science Program of He'nan Province (Grant No. 2015BZH012) and the Foundation of He'nan Educational Committee (Grant Nos. 15B630005 and 2015-ZD-048). The authors would also like to thank anonymous reviewers for their valuable comments.